AGE AND METASTATIC CHARACTERISTICS OF MAMMARY CANCER (ResearchJet Journal of Analysis and Inventions, 2021)
The aim of this study is to study the metastatic features of mammary cancer. The analysis of metastatic features of mammary cancer was carried out on the basis of the official accounting and reporting documentation of the Bukhara Regional Oncological Dispensary and together with the Bukhara Pathologic anatomical Bureau for 2013-2018 years. During the study period, 485 patients were diagnosed with mammary cancer.